THE SYNTHESIS OF SOME N-CONTAIN DERIVATIVES OF HETEROCYCLES ON THE BASE OF KETOESTHERS (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
Realized the synthesis of 1-ethoxycarbonylcyclopentanone-2 and 1-ethoxycarbonylcycloheptanone-2 through Dickmans condensation. During this reaction for diethylesthers of sebacin acid in the presence of DMFA have been received monodimethylamid of sebacin acid. In a process of interaction received ketoesthers with binucleofiles have been synthesized corresponding derivatives of pyrimidine and pyrazolone.